"The system shows us how bad it feels": special educational needs assessment in North Rhine-Westphalia, Germany. Issue 5 (20th October 2019) - Barow, Thomas; Östlund, Daniel
ABSTRACT: In the context of the North Rhine-Westphalian school reform towards an inclusive education system, this article problematises the practice of categorisation. Our research aims to investigate the assessment of special educational needs (SEN) and thereby enrich the discussion of the relation between inclusion and diagnostics. For this study, we interviewed 14 SEN investigators and five decision-makers. We discuss the results on the basis of a qualitative content analysis and against the background of Fleck's concept of thought styles. We mainly found inertia in special education traditions, expressed in the use of intelligence tests, the dominance of SEN teachers in the assessment process and the lack of participation of parents and pupils. We conclude that it is necessary to reform the SEN assessment rules. At the same time, we see major challenges in transforming existing thought styles into a more flexible and decategorising approach.